Public Health Department on Fort Riley Army Installation - Gilmore, Katelyn (My University, 2018)
Fort Riley is an Army installation in North Eastern Kansas between Junction City and Manhattan. There is an advantage to having an Army post near these cities since the Army emphasizes working with the surrounding communities and improving the environment as well as the mission of national defense (Fort Riley, KS, 2015). Although the post community is independent and geographically separate from the surrounding cities, there is often an expectation for these communities to cooperate with each other due to their proximity. The nature of military life necessitates a high-turnover in personnel at military installations like Fort Riley to support missions world-wide. This influx of personnel from diverse locations exposes the local community to health issues that they may not experience otherwise. In response, the public health department plays a key role in research and education as well as prevention and treatment in these fluid communities. The target population for the Public Health Department (PHD) on Fort Riley includes everyone who works and lives on post including active duty, retirees, families, and the civilian workforce. The following information is from the US Census Bureau for Fort Riley, KS (Population Demographics for Fort Riley, Kansas, 2016). The total population on Fort Riley is 6,638 (72% White, 15% Black, 12% Hispanic, and 65% male). A large portion, 63%, of the total population lives on Fort Riley and the average household size in Fort Riley is 2. The average age is 21.6 years with 49% of the population being 18 years and older. Education attainment for the 18-24 age range is centered around some college or an associate’s degree (65%) while 49.4% of those who are 25 years and older have some college, no degree. The median household income is $29,588. The mission of the Fort Riley PHD is “to promote health and wellness, and to prevent disease and injury of soldiers and their families, military retirees, and Army Civilian employees at Fort Riley through workplace and community health” (Big Red One, 2015). The PHD serves the community by offering various services. For example, while the Veterinary Services section specializes in the health of the animals they also educate owners on the potential impact/crossover of diseases from animals to humans. The Environmental Health section studies all vectors that can transmit disease in order to reduce prevalence of disease. The focus of Occupation Health is the well-being of the workforce (both active duty and contractors) which allows for more productivity due to a healthier workforce. All in all, each section collectively strives to work together to facilitate and maintain all aspects of health on post. With the standard of care being of top priority, the PHD strives to be the first U.S. Army post to receive accreditation from the Department of Defense. This would ensure that the services meet standards and the PHD can better serve the community. This field experience was completed in partnership with Kansas State University (KSU) and the Fort Riley Department of Public Health. After years of partnership, the practicum process has been streamlined and a schedule laid out for each student. This allows for so that the requirements for each segment of the field experience are met in a timely manner. Students gain experience within each sector of the Public Health Department throughout all components from contact hours that allow for shadowing and hands on experience for completing on-post projects with the departments. The program gives KSU students an inclusive experience that would be hard to find in other Public Health Departments. Students gain experience in a community that has unique needs compared to off-post communities.
Keywords: Fort Riley; Public Health Department